Implementasi Pendidikan Akhlak Santri Di Pondok Pesantren Modern El-Fira - Nafisah, Ulfatun; Yahya, Slamet (Lembaga Penelitian dan Pendidikan Mandala, 2022)
This study aims to determine the morals of students at the el-Fira Modern Islamic Boarding School located in Karanganjing, Purwanegara Utara Purwokerto, Banyumas, namely in that cottage there are a lot of students and each student must have different morals, not all students can be generalized in their morals. Because each student has a different background for example from environmental factors and family factors. These factors shape the character and attitude of children. Therefore, in implementing morality, it is still in the early stages, but after being given direction and example by asatidz-asatidzah at the el-Fira Modern Islamic Boarding School, the students already refer to a positive attitude because of the cultivation of morals and examples from asatidz and asatidzah in the pesantren.